Presentase dan Intensitas Serangan Hama Kutu Putih (Paracoccuss marginatus) yang Menyerang Tanaman Adenium Spp. di Kota Denpasar - Sumartayasa, I Wayan Andi; Yuliadhi, Ketut Ayu; Sumiartha, I Ketut (Nandur; Vol 1 No 3 (2021), 2021)
Research on the Percentage and Intensity of Attacks by White flies ( Paracoccuss marginatus ) Attacking Adenium Spp. in Denpasar City. The purpose of this study was to determine the White flies ( Paracoccuss marginatus ) that attacks Adenium spp., the population of pests that attack, the percentage and intensity of attacks. Sampling was carried out purposively by photographing and observing plants attacked by pests in the Districts of West Denpasar, East Denpasar, South Denpasar and North Denpasar. The results showed that White flies ( Paracoccuss marginatus ) attacked Adenium spp. in the city of Denpasar. White flies ( Paracoccuss marginatus ) number 5468 pests, with an average attack percentage of 56.25% White flies, while the average pest attack intensity is 20% White flies.